Journalism and euthanasia: A scoping review of the literature - Costa, B. F.; Azevedo, J.; Bernardes, S. F.; Garcia-Blanco, I. (OMEGA - Journal of Death and Dying)
This scoping review systematically maps empirical research on journalism and euthanasia, filling a gap left by prior health-focused reviews by centring media studies perspectives. The analysis encompassed 30 studies indexed in Web of Science and Scopus up to October 2025, revealing a thematic emphasis on news coverage related to euthanasia, euthanasia deaths, and end-of-life decisions. Most of these studies employed qualitative content and discourse analysis methods. A strong Global North bias constrains geographic and epistemic diversity. The fragmentation across journals and scientific domains reflects an emerging but methodologically diverse interdisciplinary field. Key media frames emphasised individual autonomy and suffering alleviation while marginalising alternative viewpoints. Significant gaps remain regarding public engagement with media coverage and content production dynamics. The review advocates for geographically diverse, integrative research and evidence-based ethical guidelines. Policymakers must consider media framing’s impact on public opinion and ethical debates surrounding end-of-life care.